The Effect of Tax Planning and Company Size on Earnings Management on Manufacturing Listed in Indonesia Stock Exchange - Martogi Marojahan Sitinjak; Wilifebri. Sanra (Journal of E-business and Management Science, 2023)
This study aims to analyze the effect of tax planning and company size on earnings management. The data used in this study are the company's annual financial statements with a total sample of 41 samples taken from the annual financial statements of health subsector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The analysis used is descriptive statistical analysis and multiple linear regression analysis. The results showed that tax planning has no significant effect on earnings management while company size has a significant effect on earnings management. Simultaneously, tax planning and company size have a significant effect on earnings management.